Externally-induced bodily changes and anxiety sensitivity: a pathway to anxiety symptoms - Jurin, Tanja (Array, 2013)
Objectives: Anxiety sensitivity (AS) is a fear of adverse consequences of anxiety symptoms. Because numerous physical symptoms accompanying anxiety can also be induced by various environmental stimuli, it is of interest to determine whether high AS individuals would react with increased agitation to such bodily responses as they would to those induced by anxiogenic stimuli. This paper presents preliminary results of an experimental study aimed at exploring the physical and emotional reactions to the somatic changes induced by caffeine in high-and low AS individuals. Methods: The present study included 98 participants, selected according to results on the Anxiety Sensitivity Index (50 and 48 high and low AS individuals, respectively). Participants were randomly divided into experimental (receiving caffeine) and control (receiving a placebo) groups using a double blind procedure. Data on perceived bodily changes and accompanying emotional states were collected at two time points: 1 hour and 24 hours after receiving caffeine. Results: Participants who received caffeine perceived more bodily changes accompanied by a higher level of agitation and discomfort that lasted all day long. High AS participants who consumed caffeine reported the highest number of bodily changes and the highest level of agitation, at both time points. Results: Participants who received caffeine perceived more bodily changes accompanied by a higher level of agitation and discomfort that lasted all day long. High AS participants who consumed caffeine reported the highest number of bodily changes and the highest level of agitation, at both time points. Conclusions: These results suggest that externally induced bodily changes lead to greater levels of perceived discomfort and agitation in high AS participants, as compared to their low AS counterparts. Furthermore, this emotional state lasts even after the physiological effects of caffeine should have ended. Practical and theoretical implications of these results will be discussed.